OPTIMASI SERAT KENAF SEBAGAI FILLER BIOKOMPOSIT DENGAN ADITIF SERBUK DAUN TEMBAKAU PADA APLIKASI PAPAN GIPSUM PLAFON - Vina Fauziah (Jurnal Biofisika, 2014)
Synthesis and characterization of biocomposite gypsum board ceiling based on kenaf fiber has been performed compression molding method with variation of woven and uniform filler.  The optimum fiber concentration on the fiber are woven with 10 % kenaf fiber, 88 % matrixes gypsum, 1 % PVA (Polivinil Alcohol) and tobacco. The test resulted that the hardness and impact mechanical of the resulted product was higher than the commercial gypsum. The highest absorption of gypsum board is 25 % owned by fiber glass composite, on biocomposite with addition of tobbaco is 21 % and the lowest is 13 % on biocomposite without addition of tobbaco. The highest value on thickness development is 1.85 % owned by fiber glass composite. On biocomposite with addition of tobbaco is 1.73 % and the lowest is  0.4 % on biocomposite without addition of tobbaco. Density of biocomposite is 1.6 g cm-3, whereas density of fiber glass composite is 1.98 g cm-3. The test result showed that the kenaf’s fiber and tobbaco leaf powder is reliable to use as the filling material for the the gypsum plafon.